Effect of Oxygen Precipitation in Silicon Wafer on Electrical Characteristics of Fully Ion-Implanted n-Type PERT Solar Cells. (1st January 2019) - Tanahashi, Katsuto; Tachibana, Tomihisa; Sueoka, Koji; Moriya, Masaaki; Kida, Yasuhiro; Ustunomiya, Satoshi; Shirasawa, Katsuhiko; Takato, Hidetaka
Abstract : Fully ion-implanted n -type PERT solar cells with boron-implanted emitter and phosphorus-implanted back surface field were fabricated on the n -type silicon wafers obtained from the top part of the magnetic field-applied Czochralski ingot. It was observed that the electrical parameters are widely dispersed; among 11 solar cells, the best performing achieved 20.4% front side conversion efficiency, whereas the worst achieved 19.0%. Although the silicon wafers had low oxygen concentrations of 3–4 × 10 17 atoms/cm 3, the density of oxygen precipitates in the silicon wafers was on the order of 10 9 /cm 3 as a consequence of the fully ion-implanted n -type PERT silicon solar cell processes. In addition, it was observed that the front side conversion efficiencies of the solar cells depended on the density of oxygen precipitates. Furthermore, the behavior of the oxygen precipitation during the fabrication processes of the solar cell is discussed.